FINANCIAL LITERACY AND SHARIA BANK SERVICE USE AMONG SALAF-WAHABI IN BAGIK NYAKA SANTRI, EAST LOMBOK - Iswandi, L. Muhamad (Alif Lam : Journal of Islamic Studies and Humanities, 2024)
This essay explores the significant significance of financial literacy for the Muslim-Wahabi-Salafi group residing in East Lombok. The research is primarily concerned with the issues that arise between sharia banks and ordinary banks within Salafi-Wahhabi groups. In order to get precise findings on this subject, the author employed qualitative research methods such as observation, interviews, and documentation to collect primary data, as well as utilizing many scientific works as secondary data. Upon conducting several academic procedures, the author discovered that the level of sharia financial literacy within the community of Bagik Nyaka Santri Village, particularly within Salafi-Wahabi circles, was deemed insufficient. This has a significant influence on the utilization of sharia banking services, which is likewise quite low. Financial literacy has little impact on the utilization of sharia banking services, as individuals perceive no necessity for such services. In addition to these causes, the adoption of sharia banking services is also impacted by the ideology of the Salafi-Wahabi community, which views the utilization of both conventional and sharia banking services as imbalanced. They have a preference for retaining their own funds and do not possess any inclination towards utilizing sharia-compliant banking services.